Electronic ballast for solar power street light - Wong, Kok Chin. (2009)
Solar energy is tipped to be an alternative and practical source of energy generation to replace petroleum in the future as agreed by many energy-industry observers. The growth of photovoltaic grid-connected systems worldwide has sprouted at a tremendous rate in recent years. Though Singapore is a small country, her location is ideal for photovoltaic applications as it has abundance sunlight throughout the year except for rainy seasons.